Trichoderma-Inoculation and Mowing Synergistically Altered Soil Available Nutrients, Rhizosphere Chemical Compounds and Soil Microbial Community, Potentially Driving Alfalfa Growth - Zhang, Fengge; Xu, Xixi; Huo, Yunqian; Xiao, Yan (Frontiers in Microbiology, 2019)
Trichoderma spp. are proposed as major plant growth-promoting fungi (PGPF) to increase plants growth and productivity. Mowing can stimulate aboveground regrowth to improve plant biomass and nutritional quality. However, the synergistic effects of Trichoderma and mowing on plants growth, particularly the underlying microbial mechanisms mediated by rhizosphere soil chemical compounds, have rarely been reported. In the present study, we employed Trichoderma harzianum T-63 and conducted a pot experiment to investigate the synergistic effect of Trichoderma-inoculation and mowing on alfalfa growth, and the potential soil microbial ecological mechanisms were also explored. Alfalfa treated with Trichoderma-inoculation and/or mowing (T, M and TM) had significant (P < 0.05) increases in plant shoot and root dry weights and soil available nutrients (N, P and K), compared with those of the control (CK). Nonmetric multidimensional scaling (NMDS) demonstrated that the rhizosphere chemical compounds and soil bacterial and fungal communities were respectively separated according to different treatments. There was a clear significant (P < 0.05) positive correlation between alfalfa biomass and the relative abundance of Trichoderma (R2 = 0.3451, P = 0.045). However, Pseudomonas, Flavobacterium, Arthrobacter, Bacillus, Agrobacterium and Actinoplanes were not significantly correlated with alfalfa biomass. According to structure equation modeling (SEM), Trichoderma abundance and available P served as primary contributors to alfalfa growth promotion. Additionally, Trichoderma-inoculation and mowing altered rhizosphere soil chemical compounds to drive the soil microbial community, indirectly influencing alfalfa growth. Our research provides a basis for promoting alfalfa growth from a soil microbial ecology perspective and may provide a scientific foundation for guiding the farming of alfalfa.